Driver gene alterations in NSCLC patients in southern China and their correlation with clinicopathologic characteristics - Deng, Lingna; Li, Jinbang; Qiu, Zhanlong; Wang, Yanfen (Frontiers in Genetics, 2024)
In this study, we aimed to explore the relationship between clinicopathological features and driver gene changes in Chinese NSCLC patients.Methods: Amplification refractory mutation system PCR were used to detect the aberrations of 10 driver oncogenes in 851 Chinese NSCLC patients, and their correlation with clinicopathological characteristics also be analyzed. Moreover, three models of logistic regression were used to analyze the association between histopathology and EGFR mutation or KRAS mutation.The top two most frequently aberrant target oncogenes were EGFR (48.06%) and KRAS (9.51%). Followed by ALK (5.41%), HER2 (2.35%), MET (2.23%), RET (2.11%), ROS1 (1.88%), BRAF (0.47%), NRAS (0.24%) and PIK3CA (0.12%).Additionally, 11 (1.29%) patients had synchronous gene alterations in two genes. The main EGFR mutations were exon 21 L858R and exon 19-Del, which accounted for 45.97% and 42.79% of all EGFR mutations, respectively. Logistic regression analysis showed that the frequency of EGFR mutations was positively correlated with females, non-smokers, lung adenocarcinoma and invasive non-mucinous adenocarcinoma (IA), and negatively correlated with solid nodule, micro invasive adenocarcinoma, and solid predominant adenocarcinoma. While KRAS mutation was positively associated with males and longer tumor long diameter, and negatively correlated with lung adenocarcinoma (P < 0.05 for all).Our findings suggest that the EGFR mutations frequency was higher in females, non-smokers, lung adenocarcinoma and the IA subtype in lung adenocarcinoma patients, while KRAS mutations rate was higher in males and patients with longer tumor long diameter, and lower in lung adenocarcinoma patients.